The Role of Early Childhood Teachers in Fostering Positive Attachment in Educational Settings: A Theoretical Review from the Perspective of Developmental Psychology - Hardianti Riani Utami (Journal of Early Childhood Education Perspectives, 2025)
This literature review examines the pivotal role of early childhood teachers in fostering positive attachment relationships within educational settings, grounded in developmental psychology theory. Secure attachments between teachers and young children are essential for promoting socio-emotional well-being, cognitive development, and school readiness. Drawing on recent empirical studies and theoretical frameworks, this review highlights how teacher responsiveness, emotional availability, and consistent caregiving contribute to children’s sense of security and trust. Key indicators of positive attachment—such as proximity seeking, distress alleviation, and child-initiated interactions—are linked to improved social competence, reduced anxiety, and enhanced academic outcomes. Furthermore, the review explores the neurodevelopmental implications of teacher-child attachment, emphasizing its influence on brain regions responsible for stress regulation and executive function. The compensatory role of teachers for children experiencing insecure attachments at home is also discussed, underscoring the protective effects of sensitive and stable caregiving in educational contexts. Finally, the importance of institutional support, including low child-teacher ratios, professional development in attachment-informed pedagogy, and teacher well-being, is emphasized as critical to sustaining effective teacher-child relationships. The findings advocate for integrating attachment theory into early childhood education policy and practice to foster holistic development and resilience in young learners.